Revenue Drift, Incentives, and Effort Allocation in Social Enterprises - Theodor Vladasel; Simon C. Parker; Randolph Sloof; Mirjam C. van Praag (Institute of Labor Economics (IZA), 2022)
Revenue drift, where insufficient attention is given to economic, relative to social, goals, threatens social enterprise performance and survival. We argue that financial incentives can address this problem by redirecting employee attention to commercial tasks and attracting workers less inclined to fixate on social tasks. In an online experiment with varying incentive levels, monetary rewards succeed in directing worker effort to commercial tasks; high-powered incentives attract less prosocial employees, but low-powered incentives do not alter workforce composition. Social enterprises combining monetary rewards with a social mission not only attract more workers, but are also able to guard against revenue drift.
Keywords: D22; J33; L21; L31; 330; incentives; multitasking; experiment; social enterprise; prosociality